Significant life experiences, motivations and values of climate change educators. Issue 6 (3rd June 2019) - Howell, Rachel A.; Allen, Simon
Abstract : We present a survey of 85 people involved in climate change education and mitigation, mainly in the UK, exploring the significant life experiences (SLEs) and formative influences that have contributed to their concern about climate change and their interest in climate change education and mitigation. In contrast with the findings of a large number of previous studies of environmentalists/environmental educators, outdoor experiences during childhood were not generally a major formative influence on the respondents. Although Western children nowadays commonly have fewer opportunities to enjoy such experiences, analysis showed that the differences were not due simply to changes over time. Uniquely in research on SLEs of environmentalists/environmental educators, we also examined respondents' values and motivations, to further understand what inspires action. Social justice concerns were rated as more motivating than biospheric concerns by the sample as a whole, and altruistic and biospheric values were considered equally important as guiding principles. These findings have implications for the framing of climate change as an 'environmental' problem, and suggest that, contrary to conclusions that may have been drawn from past research, environmental education specifically directed towards stimulating engagement with climate change need not entail promoting outdoor experiences, nature connectedness, or biospheric values and motivations for action.